Industrial policy of India - "Pathak, Bachcha" (New Delhi, 2007)
Developments depends on industralisation and industrialisation depends on industry policy. The first industrial policy of the Government of India was announced in April 1948. subsequently Industrial policy resolutions 1956,1980,1990. and 1991 were announced. The book has evaluated the efficacy of different Industrial policy resolutions in industrialisation development of the nation in the background of unsatisfactory performance. The latest industrial policy resolution 1991 has been prepared under the frame work of globalisation and liberalisation. The book will be of interest of policy makers teachers and students of Economics and all of others who have interest in Indian economy.
Keywords: Industrial policy-India